Analysis of the Impact of the Covid-19 Pandemic on Indonesian Economic Growth - Dekha Dwi Harianja (Green Publisher Indonesia, 2021)
The Covid-19 pandemic has had a significant impact on every line of life, especially in the economic sector. This study aims to analyze the impact of the Covid-19 pandemic on economic growth in Indonesia. The research method used in this research is descriptive qualitative method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. Sources of data obtained through library research techniques (library studies) which refers to sources available both online and offline such as: scientific journals, books and news sourced from trusted sources. These sources are collected based on discussion and linked from one information to another. Data collection techniques used in this study were observation, interviews and documentation. This data is analyzed and then drawn conclusions. Based on the analysis of the description above, it can be concluded that Covid-19 has greatly affected and had a bad impact on various economic sectors, resulting in a decline in economic growth in Indonesia. Indonesia's economic growth decreased by 2.41% as a result of the coronavirus outbreak. This will result in an increase in the level of the state budget deficit. APBN 2020 experienced an increase in the deficit figure by 6.27% of gross domestic product.